Allegory in The Black Ball: A Literary Analysis of Cultural Representation of African Americans in US - Daikha, Rachida; Ninouh, Nacira (University of Eloued جامعة الوادي, 2024)
يهدف البحث الحالي إلى التحقق من استخدام الاستعارة في قصة رالف والدو إليسون القصيرة "الكرة السوداء" لتعكس الخلفية الثقافية للأمريكيين من أصل أفريقي في الولايات المتحدة. يشتهر إليسون باستخدامه المكثف للغة التصويرية وطريقة التمثيل الرمزية. ونجح من خلال هذه الحرفة الماهرة في إبراز الجوانب الثقافية الرئيسية وإبراز القضايا الحساسة التي كانت تضطهد الأمريكيين من أصل أفريقي بشدة أثناء إقامتهم في الولايات المتحدة في ظل قوانين جيم كرو. في "الكرة السوداء"، يركز إليسون في المقام الأول على موضوعات العنصرية والتمييز والقمع والتهجير والاستغلال والتهميش، التي عاشها الشعب الأمريكي الأفريقي في منتصف القرن العشرين. تمت ملاحظة اللغة التصويرية منذ بداية القصة والرموز موجودة في كل مشهد، مما يساعد الكاتب على تحدي المعايير الثقافية والوفاء بواجبه بطريقة مثالية. وبالتالي سيتم تحليل هذا الموضوع باستخدام نظريتي التحليل الأدبي والرمزية لدراسة التمثيلات المجازية الرئيسية للقصة. The present research aims to investigate the use of allegory in Ralph Waldo Ellison's short story “The Black Ball” to mirror the cultural background of Afro-Americans in the United States. Ellison is best known for his extensive use of figurative language and symbolic way of representation. Through this skilful craft, he succeeded to project the main cultural aspects and highlight the sensitive issues that used to heavily oppress the African Americans while living in the US under Jim Crow laws. In "The Black Ball", Ellison concentrates primarily on themes of racism, discrimination, oppression, displacement, exploitation and marginalization, which the African American people have experienced in the mid of the twentieth century. Figurative language is observed from the very beginning of the story and allegories are present in each scene, assisting the writer to challenge the cultural norms and fulfil his duty in a perfect manner. Thus, this topic will be analysed by using the theories of literary analysis and symbolism to investigate the key allegorical representations of the story.
Literature and Civilization
Keywords: الرمزية، التمثيل الثقافي، التمييز، العنصرية; Allegory; cultural representation; discrimination; racism